Small-scale gene duplications played a major role in the recent evolution of wheat chromosome 3B. Issue 1 (December 2015) - Glover, Natasha; Daron, Josquin; Pingault, Lise; Vandepoele, Klaas; Paux, Etienne; Feuillet, Catherine; Choulet, Frédéric
Abstract Background Bread wheat is not only an important crop, but its large (17 Gb), highly repetitive, and hexaploid genome makes it a good model to study the organization and evolution of complex genomes. Recently, we produced a high quality reference sequence of wheat chromosome 3B (774 Mb), which provides an excellent opportunity to study the evolutionary dynamics of a large and polyploid genome, specifically the impact of single gene duplications. Results We find that 27 % of the 3B predicted genes are non-syntenic with the orthologous chromosomes ofBrachypodium distachyon, Oryza sativa, andSorghum bicolor, whereas, by applying the same criteria, non-syntenic genes represent on average only 10 % of the predicted genes in these three model grasses. These non-syntenic genes on 3B have high sequence similarity to at least one other gene in the wheat genome, indicating that hexaploid wheat has undergone massive small-scale interchromosomal gene duplications compared to other grasses. Insertions of non-syntenic genes occurred at a similar rate along the chromosome, but these genes tend to be retained at a higher frequency in the distal, recombinogenic regions. The ratio of non-synonymous to synonymous substitution rates showed a more relaxed selection pressure for non-syntenic genes compared to syntenic genes, and gene ontology analysis indicated that non-syntenic genes may be enriched in functions involved in disease resistance. Conclusion Our results highlight the major impact of single gene duplications on the wheat gene complement and confirm the accelerated evolution of theTriticeae lineage among grasses.